Análisis y aplicación de la metodología "Design Thinking" en el desarrollo de plataformas virtuales con elementos gamificados para educación básica en la Unidad Educativa González Suárez. - Zurita Gaibor, Diana Kassandra (2022)
This article presents the development of a virtual platform with the Design Thinking methodology and gamified elements, to strengthen the teaching-learning process in the teachers of the González Suárez Educational Unit. This research arises from the need of a virtual platform with gamified elements that are free, easy to use, interactive and motivational. In this study user stories with the agile POV format, test cases to verify the functionality and abuse cases for robustness and to prevent the vulnerability of the virtual platform are used, as well as a b-Learning approach for testing in the classroom. Obtaining in the end as significant results a high and satisfactory assessment of the use of the virtual platform.